The Implementation of Bank as a Service Marketing Communication Strategy in Increasing the number of customers on blu by BCA Digital - Husada, Safaruddin; Aruman, Akhmad Edhy (LSPR Institute of Communication & Business, 2024)
Marketing communication activities through strategies to develop market penetration and brand positioning strategies are very significant efforts for blu by BCA Digital. blu is an all-in- one banking product that is a solution to answer the financial and non-financial needs of digital savvy through an interconnected digital ecosystem, as well as spreading brand awareness for the BCA Digital platform. This study aims to identify blu's marketing communication strategy with the implementation of public relations, marketing mix, efforts and challenges in their promotional activities. This research also seeks to find the most dominant form of blu's promotional efforts. Descriptive qualitative method is used in this study. The data collection was carried out through non-participant observation, in-depth interviews, literature review and archiving. Key informants were obtained through purposive sampling technique. Data analysis was carried out by means of data reduction, data presentation and verification. shows that blu is very dominant and active in carrying out digital promotional mixes through mobile application platforms, social media and establishing collaborative partnerships with various communities to build ecosystems. In addition, blu also has the goal of educating its multi-segment target audience to make blu's digital banking relevant to everyday life. blu launched a mobile banking application which as of December 2022, the users achieve more than 1.1 million people. This achievement could not have been separated from good collaboration and integration with fintech partners, cooperation with companies and various universities with bank as a service or blu access is installed in the partner’s applications.